Religious Officials' knowledge, attitude, and behavior towards smoking and the new tobacco law in Kahramanmaras, Turkey - Sucakli, Mustafa Haki (BioMed Central, 2011)
BACKGROUND: Tobacco control effort should be first started in people that are looked upon as role models for the general population. We aimed to determine the knowledge, attitude, and behavior of religious officials towards smoking and the new tobacco law. METHOD: The study group was comprised of 492 Imams and 149 Quran course instructors working in Kahramanmaras city of Turkey, 641 religious officials in total, and our survey form was applied on 406 (63.3%) of those religious officials who agreed to participate in the study. RESULTS: Twenty-eight (6.9%) participants were current smokers and 35 (8.6%) were ex-smokers. 99.8% of the religious officials believed that smoking was harmful and/or prohibited in terms of religion. While 43.6% respondents thought smoking was "haram" (forbidden by Islam), 56.2% believed it was "makruh" (something regarded as reprehensible, though not forbidden by God according to Islam). 85.2% of the participants were aware of the recent tobacco law. 55.5% of the respondents, who were aware of the recent tobacco law, evaluated their knowledge level on the law as adequate, whereas 44.5% evaluated it as inadequate 92.4% of the participants noted that religious officials should play active roles in tobacco control effort. CONCLUSION: Smoking rate among religious officials is much lower than that of general public. In order to help religious officials to take a more active role on this issue, they should be trained on the subject and appropriate platforms should be established.